Molecular Characterization of Zinc (Zn) Resistant Bacteria in Banger River, Pekalongan, Indonesia - Sasi, Fitri Arum; Kusumaningrum, Hermin Pancasakti; Budiharjo, Anto (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Indigenous bacteria are able to remove the metals contamination in environment. This study aimed to assess the resistance of bacterial species to Zinc (Zn) in Banger River, Pekalongan City. The bacteria from three different parts of Banger River were isolated and inoculated in Zn-selective medium. Then, molecular identification to determine the bacteria species was conducted using polymerase chain reaction (PCR) by applying forward-reverse 16SrRNA gene primers. The sequences analysis was conducted using MUSCLE and MEGA6. There were seven dominant species that possibly resistant to Zn. Approximately, every isolate could reach more than 95 % from 2000 ppm of Zn in the medium. The higher absorption of Zn was found in Z5 isolate. The seven bacteria species were clustered into nine genera i.e. Klebsiela, Xenorhabdus, Cronobacter, Enterobacter, Escherichia, Shigella and Sporomusa known as Gram Negative bacteria and Clostridium and Bacillus as Gram Positive bacteria. In Gram Positive bacteria, especially Bacillus sp, carboxyl group in peptidoglycan play a role as metal binder. In Gram-negative bacteria, lipopolysaccharide (LPS) which is highly anionic component on the outer membrane, able to catch the Zn. Besides that, Enterobacter activates endogen antioxidants such as glutathione peroxidase (GSHPx), glutathione reductase (GR), catalase (CAT) and superoxide dismutase (SOD). The research found there was possible seven novel indigenous bacteria species in Banger that able to remove Zn from the sediment extremely. This finding can be developed as an eco-friendly approach to reduce metals pollution using local microorganisms.